Meningkatkan Kemampuan Berbicara Siswa Kelas XI PM 1 dengan Strategi Pembelajaran Berdiferensiasi - Sada, Siti Haluma; Astuti, Eko Widdy; Astutik, Indri (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2024)
It is common knowledge that graduates of vocational schools (SMK) are oriented toward the working world. Undoubtedly, English is highly essential to support the competence of these graduates. However, regrettably, English remains a daunting challenge, especially when it comes to speaking skills. Therefore, differentiated learning is of great importance to be implemented. Differentiated learning is a teaching strategy oriented toward the learning needs of students. In this research, the researcher employed differentiated learning, focusing on differentiating content, processes, and environments, with reference to addressing various learning styles. The aim of this research was to enhance the speaking skills of the 11th-grade PM 1 class using differentiated learning. The study utilized the Class Action Research (CAR) method, consisting of two cycles. Each cycle encompassed four stages: planning, acting, observing, and reflecting. Collaborative action research was conducted, involving the collaboration of the researcher and an English teacher serving as a mentor. Data collection involved tests, observations, and presentation assessments. The data analysis employed quantitative descriptive analysis, which presented the results in a descriptive form for quantitative data. Based on the research conducted, it was found that students' speaking skills were very low. In the pretest stage, their average score was 60. In the first cycle, there was an improvement to 70, and in the second cycle, there was a further increase to 85. From these results, it can be concluded that the use of differentiated learning is highly effective in improving the speaking skills of SMK Negeri 1 Banyuwangi 11th-grade PM 1 students.